2018
DOI: 10.1038/s41380-018-0045-1
|View full text |Cite
|
Sign up to set email alerts
|

Impaired insulin signaling in unaffected siblings and patients with first-episode psychosis

Abstract: Patients with psychotic disorders are at high risk for type 2 diabetes mellitus, and there is increasing evidence that patients display glucose metabolism abnormalities before significant antipsychotic medication exposure. In the present study, we examined insulin action by quantifying insulin sensitivity in first episode psychosis (FEP) patients and unaffected siblings, compared to healthy individuals, using a physiological-based model and comprehensive assessment battery. Twenty-two unaffected siblings, 18 F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 68 publications
2
25
0
1
Order By: Relevance
“…While it is unknown how antipsychotic medications impact brain IR, studies suggest that adults with SZ have an increased risk for diabetes or impaired glucose metabolism regardless of medication status (Rajkumar et al, 2017), glucose homeostasis is altered from illness onset of SZ (Pillinger et al, 2017), and glycemic abnormalities are likely intrinsic to the illness beyond the known effects of medication, lifestyle, and health care access (Perry et al, 2016). Finally, a study in patients with first episode psychosis, unaffected patient siblings, and HC found that patients and their siblings had lower sensitivity to insulin than HC (Chouinard et al, 2018). Abnormal peripheral glucose metabolism or insulin signaling may be an increased risk factor for psychosis and independent of treatment effects.…”
Section: Discussionmentioning
confidence: 99%
“…While it is unknown how antipsychotic medications impact brain IR, studies suggest that adults with SZ have an increased risk for diabetes or impaired glucose metabolism regardless of medication status (Rajkumar et al, 2017), glucose homeostasis is altered from illness onset of SZ (Pillinger et al, 2017), and glycemic abnormalities are likely intrinsic to the illness beyond the known effects of medication, lifestyle, and health care access (Perry et al, 2016). Finally, a study in patients with first episode psychosis, unaffected patient siblings, and HC found that patients and their siblings had lower sensitivity to insulin than HC (Chouinard et al, 2018). Abnormal peripheral glucose metabolism or insulin signaling may be an increased risk factor for psychosis and independent of treatment effects.…”
Section: Discussionmentioning
confidence: 99%
“…One contributor to comorbidity between cardiometabolic disorders and schizophrenia could be shared genetic susceptibility ( Lin and Shuldiner, 2010 ). Risk of insulin resistance (IR) ( Chouinard et al, 2019 ) and impaired glucose tolerance ( Ferentinos and Dikeos, 2012 ), two key precursors of T2DM, are higher in unaffected relatives of patients with psychosis compared with controls. People with comorbid schizophrenia and T2DM have a higher genetic predisposition for both disorders compared to controls ( Hackinger et al, 2018 ), and an association between genetic predisposition for schizophrenia and IR has been reported in a clinical sample ( Tomasik et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A further aspect to consider is that, due to the relationship between the immune and the metabolic system, high levels of peripheral inflammation are generally associated with metabolic abnormalities in both the general population and in FEP patients (Russell et al, 2015) (Petrikis et al, 2015;Pillinger et al, 2017a;Pillinger et al, 2017b;S et al, 2013). More interestingly, weight gain, increased visceral fat and impaired glucose metabolism have been detected also in drug naïve patients (Correll et al, 2014), with altered insulin signaling being present also in unaffected siblings (Chouinard et al, 2018).…”
mentioning
confidence: 96%